An Analysis of the Effectiveness of Zakat, Infaq and Sadaqah Fund Management in a Large Mosque in Taipei - Elinah; Saiful Anwar (Jurnal Multidisiplin Madani, 2024)
Taiwan is a country with a religious composition dominated by adherents of Buddhism, Taoist beliefs, Christianity, and practices of animism or other local beliefs, while adherents of Islam are 0.3% of the total population. The purpose of this study was to analyze the management of zakat infaq and alms funds at the Taipei Grand Mosque, as well as to analyze the effectiveness of the management of zakat infak and alms funds. The research results prove that managing zakat funds, both fundraising and channeling funds for the Taipei Grand Mosque, does not carry out planning and coordination. Mosque management in collecting funds and distributing them is only passive waiting for muzaki to come to the mosque to pay zakat, infaq, and alms. Fundraising is done by opening an account at a bank and a charity box in front of the mosque. Muslim communities who are going to pay zakat, can do it by bank transfer or come directly to the mosque by handing over money in cash or putting it through a charity box. The distribution of zakat funds can also be carried out by transferring funds to a bank and distributing them in cash at the Taipei Great Mosque. Funds are distributed mainly to mustahik who are around the mosque. The distribution of zakat funds is carried out transparently, regardless of nationality, ethnicity, or race, as long as the Muslim Community is included in the eight a snap. Supervision or monitoring of fundraising is carried out by the internal management of the mosque, both routinely and specifically. The government conducts audits of incoming and outgoing funds so that every mosque in Taipei is required to submit financial reports to the government